2009
DOI: 10.1242/dev.017178
|View full text |Cite
|
Sign up to set email alerts
|

Blastocyst lineage formation, early embryonic asymmetries and axis patterning in the mouse

Abstract: The investigation into lineage allocation and early asymmetries in the pre-and peri-implantation mouse embryo is gaining momentum. As we review here, new insights have been gained into the cellular and molecular events that lead to the establishment of the three lineages of the blastocyst, to the determination of the origin and the fates of the visceral endoderm in the peri-implantation mouse embryo, and to the generation of cellular and molecular activities that accompany the emergence of asymmetries in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
527
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 562 publications
(543 citation statements)
references
References 104 publications
9
527
0
7
Order By: Relevance
“…As a result, we found that OCT4 and CDX2 mRNA expression in day 6 compacted morulae were not different among the treatment groups. In murine embryos, it has been shown that Oct4 is required for specifying the pluripotent cells of the ICM, that Cdx2 is required for the commitment, integrity and differentiation of TE lineage and that these two transcription factors mutually suppress the expression of each other and contribute to establishment of the ICM and TE lineage [27]. The present results showed that the deficiency of methionine metabolism did not affect the expression of OCT4 and CDX2.…”
Section: Discussionsupporting
confidence: 38%
See 1 more Smart Citation
“…As a result, we found that OCT4 and CDX2 mRNA expression in day 6 compacted morulae were not different among the treatment groups. In murine embryos, it has been shown that Oct4 is required for specifying the pluripotent cells of the ICM, that Cdx2 is required for the commitment, integrity and differentiation of TE lineage and that these two transcription factors mutually suppress the expression of each other and contribute to establishment of the ICM and TE lineage [27]. The present results showed that the deficiency of methionine metabolism did not affect the expression of OCT4 and CDX2.…”
Section: Discussionsupporting
confidence: 38%
“…At the morula-to-blastocyst transition, mammalian embryos undergo the first lineage segregation into the inner cell mass (ICM) and trophectoderm (TE) [27,28]. The repression of morula-to-blastocyst transition by ethionine prompted us to investigate the expression levels of cell lineagerelated transcription factors involved in blastocyst formation.…”
Section: Discussionmentioning
confidence: 99%
“…The proximodistal polarity of the E5.5 embryo is transformed into anterior-posterior polarity at E6.5 through the migration of DVE cells from distal to anterior positions, where they take the name of anterior visceral endoderm cells (AVE), and the formation of the primitive streak in the posterior epiblast (reviewed by Rossant and Tam, 2009;Takaoka and Hamada, 2012). The transcription factor brachyury (T ) marked the posterior epiblast and the nascent primitive streak both in control and N1ICD epi littermates (n=3; Fig.…”
Section: Notch Activation Does Not Affect Anterior-posterior Polaritymentioning
confidence: 99%
“…7f). At E6.2, mouse embryos establish the anterior VE (AVE), a specific repertoire of the VE 39 . The AVE expresses and secretes the Cerl and Lefty-1, which suppress Nodal signalling in the epiblast.…”
Section: Delivery Of Endosomes To Vacuoles Requires Rab7 Functionmentioning
confidence: 99%